If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x = -5x + -8 Reorder the terms: 3x = -8 + -5x Solving 3x = -8 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 3x + 5x = -8 + -5x + 5x Combine like terms: 3x + 5x = 8x 8x = -8 + -5x + 5x Combine like terms: -5x + 5x = 0 8x = -8 + 0 8x = -8 Divide each side by '8'. x = -1 Simplifying x = -1
| 9x-2(3x+1)=x+1 | | -3=-9x-3 | | .09x^2-2.007x+.00012=0 | | 4(x-2)=3(x-2) | | 1/4(x-8)+7 | | x-32=-27 | | 2x-4y=12fory | | 2r+-6r=12 | | Ym+3=n | | -3m+4m-2=m-2 | | 5m+7.75=40.25 | | 5(h-1)=2(h-4)-6 | | 7/8*16 | | -6w+4=-2(3w-2) | | x/9+x=5/8 | | 8(12-y)+4y=12y-96 | | -3+2/3=4 | | 18-r=48 | | 12k+11(3k-5)= | | -9y-7=-4y-12 | | 3y-y=14 | | g-16= | | x*x=7.5*7.5+(x-1)*(x-1) | | 5y-2=15 | | t-30=14-3t | | 3(2x+2)=10x+1-4x+5 | | -x^2-.18x+.045=0 | | 6x+14=2x-6 | | 2x-2=14x+4 | | 3(c-1)=7 | | X+7-4=-2x+5x+1 | | 17-9m-m=23 |